Genetic analysis of CHARGE syndrome identifies overlapping molecular biology. - Moccia, Amanda; Srivastava, Anshika; Skidmore, Jennifer M; Bernat, John A; Wheeler, Marsha; Chong, Jessica X; Nickerson, Deborah; Bamshad, Michael; Hefner, Margaret A; Martin, Donna M; Bielas, Stephanie L (Genet Med, 2018)
PURPOSE: CHARGE syndrome is an autosomal-dominant, multiple congenital anomaly condition characterized by vision and hearing loss, congenital heart disease, and malformations of craniofacial and other structures. Pathogenic variants in CHD7, encoding adenosine triphosphate-dependent chromodomain helicase DNA binding protein 7, are present in the majority of affected individuals. However, no causal variant can be found in 5-30% (depending on the cohort) of individuals with a clinical diagnosis of CHARGE syndrome. METHODS: We performed whole-exome sequencing (WES) on 28 families from which at least one individual presented with features highly suggestive of CHARGE syndrome. RESULTS: Pathogenic variants in CHD7 were present in 15 of 28 individuals (53.6%), whereas 4 (14.3%) individuals had pathogenic variants in other genes (RERE, KMT2D, EP300, or PUF60). A variant of uncertain clinical significance in KDM6A was identified in one (3.5%) individual. The remaining eight (28.6%) individuals were not found to have pathogenic variants by WES. CONCLUSION: These results demonstrate that the phenotypic features of CHARGE syndrome overlap with multiple other rare single-gene syndromes. Additionally, they implicate a shared molecular pathology that disrupts epigenetic regulation of multiple-organ development.
Keywords: Adolescent; Adult; Carrier Proteins; CHARGE Syndrome; Child; Child, Preschool; Cohort Studies; DNA Helicases; DNA-Binding Proteins; E1A-Associated p300 Protein; Epigenesis, Genetic; Female; Genetic Testing; Humans; Infant; Male; Mutation; Neoplasm Proteins; Phenotype; Repressor Proteins; RNA Splicing Factors

Evidence for replicative mechanism in a CHD7 rearrangement in a patient with CHARGE syndrome. - Vatta, Matteo; Niu, Zhiyv; Lupski, James R; Putnam, Philip; Spoonamore, Katherine G; Fang, Ping; Eng, Christine M; Willis, Alecia S (Am J Med Genet A, 2013)
Haploinsufficiency of CHD7 (OMIM# 608892) is known to cause CHARGE syndrome (OMIM# 214800). Molecular testing supports a definitive diagnosis in approximately 65-70% of cases. Most CHD7 mutations arise de novo, and no mutations affecting exon-7 have been reported to date. We report on an 8-year-old girl diagnosed with CHARGE syndrome that was referred to our laboratory for comprehensive CHD7 gene screening. Genomic DNA from the subject with a suspected diagnosis of CHARGE was isolated from peripheral blood lymphocytes and comprehensive Sanger sequencing, along with deletion/duplication analysis of the CHD7 gene using multiplex ligation-dependent probe amplification (MLPA), was performed. MLPA analysis identified a reduced single probe signal for exon-7 of the CHD7 gene consistent with potential heterozygous deletion. Long-range PCR breakpoint analysis identified a complex genomic rearrangement (CGR) leading to the deletion of exon-7 and breakpoints consistent with a replicative mechanism such as fork stalling and template switching (FoSTeS) or microhomology-mediated break-induced replication (MMBIR). Taken together this represents the first evidence for a CHD7 intragenic CGR in a patient with CHARGE syndrome leading to what appears to be also the first report of a mutation specifically disrupting exon-7. Although likely rare, CGR may represent an overlooked mechanism in subjects with CHARGE syndrome that can be missed by current sequencing and dosage assays.
Keywords: Abnormalities, Multiple; CHARGE Syndrome; Child; DNA Helicases; DNA Replication; DNA-Binding Proteins; Exons; Female; Gene Deletion; Haploinsufficiency; Humans; Mutation